Fine root dynamics and associated nutrient flux in Sal dominated forest ecosystems of Central Himalaya, India - Pandey, Rachita; Bargali, Surendra Singh; Bargali, Kiran; Karki, Himani; Kumar, Munesh; Sahoo, U. K. (Frontiers in Forests and Global Change, 2023)
The belowground systems of trees have a major role in forest functioning through absorption of water and nutrient cycling. This study deals with the fine root dynamics including fine root biomass, necromass, production, turnover, and nutrient return in transitional Sal (Shorea robusta Gaertn. f.) dominated sub-tropical forest ecosystems of Central Himalaya, India. Four sites namely, Site-1 (Kaladhungi), Site-2 (Fatehpur), Site-3 (Ranibagh), Site-4 (Amritpur) were selected in Sal forest within an elevational range between 405 and 580 m above sea level. The dominant and associated co-dominant species were selected from each site for the estimation of fine root dynamics by using sequential core and ingrowth core methods. The results revealed that the fine root biomass, necromass, and production were significantly (p < 0.05) affected by location, seasons, and soil properties. The fine root biomass and production decreased with increasing soil depth and also influenced by stand characteristics including tree density and basal area. The rainy season was most productive with maximum fine root biomass (507.37 kg ha–1) as well as fine root production (600.26 kg ha–1 season–1) in the dominant tree species S. robusta. Among the associated co-dominant tree species highest fine root biomass (330.48 kg ha–1) and fine root production (410.04 kg ha–1 season–1) was reported for Tectona grandis L. during the rainy season, while lowest fine root biomass (126.72 kg ha–1) and fine root production (195.59 kg ha–1 season–1) in the Glochidion velutinum Wight tree species during the winter season. Annual fine root production ranged from 460.26 to 1583.55 kg ha–1 yr –1, while turnover rate varied from 1.37 to 4.45 yr–1 across all the studied sites. The fine roots added carbon input of 154.38 to 564.20 kg ha–1 yr–1 and nitrogen input of 6.58 to 24.34 kg ha–1 yr–1 to the soil through annual flux. The study improves our understanding on fine root parameters under the influence of sites, soils and seasonal and spatial variation. The return of nutrients to the soil through fluxes from the roots illustrates the role of fine roots in carbon and nitrogen cycling of the forests and this potential can be harnessed to assess the long-term carbon and nitrogen pool estimations in forests and to plan and manage the forest ecosystems.